2018
DOI: 10.1016/j.omtn.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA 00473 Is Involved in Preeclampsia by LSD1 Binding-Regulated TFPI2 Transcription in Trophoblast Cells

Abstract: Preeclampsia (PE) is a syndrome manifested by high blood pressure that could develop in the latter half of pregnancy; however, the underlying mechanisms are not understood. Recent evidence points to the function of noncoding RNAs (ncRNAs) as novel regulators of the invasion, migration, proliferation, and apoptosis of trophoblasts involved in the development of placental vasculature. Here, we investigated the role of long intergenic ncRNA 00473 (linc00473) in PE and the associated molecular mechanisms. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…The decreased level of EGFR Antisense RNA1 (EGFR-AS1) in PE had the potential to decrease the level of EGFR in trophoblast cells and the phosphorylation levels of downstream proteins in JAK/STAT signal pathway, followed by inducing the occurrence of PE [57]. The level of linc00473 was decreased in the placental tissues of severe PE women, linc00473 downregulation in trophoblast cells substantially reduced cell proliferation, together with increasing cell apoptosis, while linc00473 upregulation increased cell proliferation through the attenuation of tissue factor pathway inhibitor 2 (TFPI2) by combing to LSD1 [58]. LncRNA PVT1 downregulation substantially decreased cell proliferation; besides inducing the cell cycle as well as cell apoptosis, the mechanism of PVT1 was through the regulation of angiopoietin-like 4 (ANGPTL4) as well as Ezh2 [59].…”
Section: Lncrnas Affect Cellular Functions Of Trophoblast Cellsmentioning
confidence: 99%
“…The decreased level of EGFR Antisense RNA1 (EGFR-AS1) in PE had the potential to decrease the level of EGFR in trophoblast cells and the phosphorylation levels of downstream proteins in JAK/STAT signal pathway, followed by inducing the occurrence of PE [57]. The level of linc00473 was decreased in the placental tissues of severe PE women, linc00473 downregulation in trophoblast cells substantially reduced cell proliferation, together with increasing cell apoptosis, while linc00473 upregulation increased cell proliferation through the attenuation of tissue factor pathway inhibitor 2 (TFPI2) by combing to LSD1 [58]. LncRNA PVT1 downregulation substantially decreased cell proliferation; besides inducing the cell cycle as well as cell apoptosis, the mechanism of PVT1 was through the regulation of angiopoietin-like 4 (ANGPTL4) as well as Ezh2 [59].…”
Section: Lncrnas Affect Cellular Functions Of Trophoblast Cellsmentioning
confidence: 99%
“… 59 We chose HTR-8SV/neo cells for cellular functional studies because this cell line is widely used in previous studies on the pathogenesis of PE. 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 We overexpressed or knocked out this gene in this placenta-derived trophoblast cell line and found that INHBA-AS1 prohibited the invasion, migration, and proliferation ( Figures 2 A–2D, 3 A, and 3B) and promoted apoptosis ( Figures 3 C and 3D). These results demonstrated that INHBA-AS1 may participate in the pathogenesis of PE through inhibiting trophoblast invasion, migration, and proliferation, which may lead to shallow implantation of the placenta.…”
Section: Discussionmentioning
confidence: 96%
“…In the present study, LINC00473, also known as LNC473, C6orf176, bA142J11.1, and is located in the 6q27 region and LINC00473, was downregulated in the hBMSCs following osteogenic differentiation. It has been found that LINC00473 was involved in the development of a number of diseases including preeclampsia ( 38 ), colorectal cancer ( 39 ), gastric cancer ( 40 ) and others. It has been demonstrated that LINC00473 is involved in the pathogenesis and development of preeclampsia and may be a candidate biomarker, as well as a therapeutic target for preeclampsia ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that LINC00473 was involved in the development of a number of diseases including preeclampsia ( 38 ), colorectal cancer ( 39 ), gastric cancer ( 40 ) and others. It has been demonstrated that LINC00473 is involved in the pathogenesis and development of preeclampsia and may be a candidate biomarker, as well as a therapeutic target for preeclampsia ( 38 ). Wang et al found that LINC00473 promoted Taxol resistance via miR-15a in colorectal cancer ( 39 ).…”
Section: Discussionmentioning
confidence: 99%